Diagnosis of Rare Synchronous Pleural and Peritoneal Mesothelioma in a Domesticated Canine - Saravanan, S.; Kumar, V.; Ramprabhu, R.; Sundararajan, R. C. (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
This paper reports a rare incidence of invasive mesothelioma in both thoracic and peritoneal cavities of a two and a half year old Labrador Retriever dog and its diagnosis by cytological analysis, radiography and ultrasonogram. Malignant mesotheliomas most often affect the pleura and tend to spread locally within the originating cavity. Mesotheliomas are already rare diseases, and cases with synchronous pleural and peritoneal involvement are scarce in the literature. A male Labrador Retriever dog of two years and six months old was presented to the Teaching Veterinary Clinical Complex Veterinary College and Research Institute, Tirunelveli (Tamil Nadu, India) with the complaint of the distended ventral abdomen, respiratory distress, and exercise intolerance since 4 months and hyporexia since 7 days. The case was treated with parenteral administration of amoxicillin and cloxacillin @ 22 mg/kg b.wt. to prevent complications like peritonitis, furosemide @ 4 mg/kg b.wt. to reduce the ascites in the abdomen, prednisolone @ 0.5 mg/kg b.wt. to reduce neoplastic response (lymphocytosis), multiple amino acids (Astymin®) to alleviate hypoalbuminemia. Therapeutic options for mesothelioma include surgical resection, radiotherapy, and chemotherapy, though a low incidence of the cases in dogs leads to difficulty in the assessment of the therapeutic efficacy of drugs.